(untitled) (Cuadernos de Extensión Universitaria de la UNLPam, 2022)
The next paper will analyze the actions carried out by the National University of the Center of the Province of Buenos Aires (UNICEN) during the first two years of the Covid-19 pandemic (years 2020 and 2021). This analysis will also provide a glimpse and a general reflection on the impact of the pandemic on university outreach and on how universities played a leading role in the fight against the health, social and economic crisis it generated.